Fast plasma sintering delivers functional graded materials components with macroporous structures and osseointegration properties - Godoy, Roberta Ferro; Coathup, M. J.; Blunn, G. W.; Alves, A. L.G. [UNESP]; Robotti, P.; Goodship, A. E. (Forum Multimedia Publishing, 2016)
We explored the osseointegration potential of two macroporous titanium surfaces obtained using fast plasma sintering (FPS): Ti macroporous structures with 400-600 µmØ pores (TiMac400) and 850-1000 µmØ pores (TiMac850). They were compared against two surfaces currently in clinical use: Ti-Growth® and air plasma spray (Ti-Y367). Each surface was tested, once placed over a Ti-alloy and once onto a CoCr bulk substrate. Implants were placed in medial femoral condyles in 24 sheep. Samples were explanted at four and eight weeks after surgery. Push-out loads were measured using a material-testing system. Bone contact and ingrowth were assessed by histomorphometry and SEM and EDX analyses. Histology showed early osseointegration for all the surfaces tested. At 8 weeks, TiMac400, TiMac850 and Ti-Growths® showed deep bone ingrowth and extended colonisation with newly formed bone. The mechanical push-out force was equal in all tested surfaces. Plasma spray surfaces showed greater bone-implant contact and higher level of pores colonisation with new bone than FPS produced surfaces. However, the void pore area in FPS specimens was significantly higher, yet the FPS porous surfaces allowed a deeper osseointegration of bone to implant. FPS manufactured specimens showed similar osseointegration potential to the plasma spray surfaces for orthopaedic implants. FPS is a useful technology for manufacturing macroporous titanium surfaces. Furthermore, its capability to combine two implantable materials, using bulk CoCr with macroporous titanium surfaces, could be of interest as it enables designers to conceive and manufacture innovative components. FPS delivers functional graded materials components with macroporous structures optimised for osseointegration.
Keywords: Bone colonisation; Fast plasma sintering; Implant; Macroporous; Plasma spray; Sheep; Surgery; Titanium